2020
DOI: 10.31590/ejosat.732239
|View full text |Cite
|
Sign up to set email alerts
|

Yoğunluk Fonksiyonel Teorisi ile Kontrast Madde Iomeprol Üzerinde Çözücü Etkileri

Abstract: Contrast compounds, also called contrast agents or contrast media are substances that temporarily change the way X-rays or other imaging tools interact with the body. Iomeprol is a nonionic monomeric iodinated contrast medium. Optimized geometries of Iomeprol, HOMO-LUMO energy, energy gap, global chemical indices, total energy, nonlinear optical and Natural Bond Orbital (NBO) analysis in the gas phase and in solvents (chloroform, acetic acid, ethanol, DMF, DMSO and water) were obtained based on Density Functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…They reported that the inclusion of solvents for Iopamidol causes the HOMO values to become more negative. 21 The lowest LUMO energy of -2.29 eV was found to be in water indicating that the molecule will be the best accept electron in water compare to the gas phase and other solvents. The energy gap is used in determining molecular electrical transport properties.…”
Section: Resultsmentioning
confidence: 97%
“…They reported that the inclusion of solvents for Iopamidol causes the HOMO values to become more negative. 21 The lowest LUMO energy of -2.29 eV was found to be in water indicating that the molecule will be the best accept electron in water compare to the gas phase and other solvents. The energy gap is used in determining molecular electrical transport properties.…”
Section: Resultsmentioning
confidence: 97%